Health promotion behaviours of pregnant women and spiritual well‐being: Mediatory role of pregnancy stress, anxiety and coping ways - Mohammad Chehrazi; Mahbobeh Faramarzi; Somayeh Abdollahi; Maria Esfandiari; Shiva Shafie rizi (Wiley, 2021)
Abstract Aim Little is known about the link between spiritual well‐being and health promotion behaviours in pregnant women. The study aimed to explore the direct and indirect effects of spirituality on health promotion behaviours with the mediatory roles of pregnancy stress, anxiety and coping ways. Design Cross‐sectional. Methods Two hundred women aged above 18 years completed Spiritual Well‐Being scale (SWBS), State‐Anxiety Inventory (SAI), Promoting Lifestyle Profile (HPLP), Prenatal Coping Inventory (Nu‐PCI) and Revised Prenatal Distress Questionnaire (NuPDQ). Results Spirituality directly and negatively affected the state anxiety (β = −.41; p < .001) and NuPDQ (β = −.36; p < .001). Health promotion behaviours were negatively related to state anxiety (β = −.36; p < .001) and positively to planning‐preparation coping (β = .23; p = .001). Spirituality had a significant indirect effect on health promotion behaviours (β = .33; p < .001), mediated through its association with state anxiety and planning‐preparation coping. Thus, health professionals are proposed to consult pregnant women on the benefits of spirituality for improving healthy behaviours.